2018
DOI: 10.1007/s00418-018-1740-3
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular criteria allow the identification of putative germ stem cells in a lophotrochozoan, the Pacific oyster Crassostrea gigas

Abstract: While our knowledge of bivalve gametogenesis recently progressed, data on early stages of gametogenesis remain to be developed, especially when dealing with germinal stem cells (GSC) and their niche in these organisms. Here, we wish to develop a strategy to identify putative GSC in Pacific oyster Crassostrea gigas based on morphological criteria combined with vasa marker expression. A histological quantitative approach, based on stereology, allowed us to identify two types of early germ cells in the germinal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…It corresponds to the mature reproductive stage where spermatids and spermatozoa in males or pre-vitellogenic and vitellogenic oocytes in females constitute the majority of the germ cells present in the tubules [6,27]. However, at this stage, putative germinal stem cells are also present at the edge of the tubules [14] which, under the impulse of sex-determining genes will initiate a new male or female gonadal differentiation while animals are still mature and ready to spawn [45,46,51,53]. Thus, further investigations will be necessary to precisely characterize the 57 factors we found and define their spatial and temporal expression in order to determine which ones are involved in the oyster's sex determination or early differentiation.…”
Section: Genes Differentially Expressed Between Sexes During the Sex-determining/−differentiating Time Window In C Gigasmentioning
confidence: 99%
See 1 more Smart Citation
“…It corresponds to the mature reproductive stage where spermatids and spermatozoa in males or pre-vitellogenic and vitellogenic oocytes in females constitute the majority of the germ cells present in the tubules [6,27]. However, at this stage, putative germinal stem cells are also present at the edge of the tubules [14] which, under the impulse of sex-determining genes will initiate a new male or female gonadal differentiation while animals are still mature and ready to spawn [45,46,51,53]. Thus, further investigations will be necessary to precisely characterize the 57 factors we found and define their spatial and temporal expression in order to determine which ones are involved in the oyster's sex determination or early differentiation.…”
Section: Genes Differentially Expressed Between Sexes During the Sex-determining/−differentiating Time Window In C Gigasmentioning
confidence: 99%
“…This species is known as a sequential hermaphrodite [10,15,31] that displays both genetic and environmental sex determination [12,24,31,33,45,52]. The time window of sex determination / early gonadal differentiation in adults C. gigas has been defined between the end of a cycle, when the animals are mature and after spawning, at the beginning of a new cycle (respectively stages 3 and 0 according to [6]), two stages presenting germinal stem/progenitor cells [14] which, under the impulse of sex-determining genes will initiate a new male or female gonadal differentiation [22,45,46,51,53]. However, at both stages, the future sex of the oysters is unknown, especially as the oyster is devoid of identifiable heteromorphic sex chromosomes.…”
mentioning
confidence: 99%
“…The annual renewal of gonads in bivalves is preceded by proliferation of Vasa-tagged cells within the intestinal epithelium (Milani et al 2017 , 2018 ; but see Cherif-Feildel et al 2019 ). These cells were supposed to migrate later in the connective tissue, where they divide and eventually differentiate into germ cells and gametes inside newly formed acini.…”
Section: Discussionmentioning
confidence: 99%
“…Anadara kagoshimensis and Crassostrea gigas (Pteriomorphia), suggesting a shared pattern for the whole class (Milani et al 2017 ). However, a recent study of Cherif-Feildel and colleagues ( 2019 ) failed to observe labelling of the Vasa homologue in both the intestinal and the connective tissues of C. gigas but observed Vasa exclusively in early germ cells localized in the gonads. Moreover, in the germinal epithelium, the authors observed Vasa-tagged potential germ stem cells surrounded by what appeared to be a germinal niche of specialized somatic cells.…”
Section: Introductionmentioning
confidence: 94%
“…Homologs of vasa, piwi, and tudor genes are an example of conserved genes expressed in germ granules, involved both in germline specification and in germ cell differentiation (Fierro-Constaín et al, 2017;Juliano et al, 2010). Moreover, since they are expressed in germ cells (Juliano et al 2010), they are used also to recognize germ cell localization (Cavelier et al, 2017;Cherif-Feildel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%